(untitled) (Economic and Political Thought, 2013)
Logistics is a new discipline of management. During the last decades its growth has been very dynamic. The thesis proposed in this paper states that logistics develops in the direction of systems thinking paradigm. To justify this statement, the main systems thinking assumptions have been presented; the definition of logistics, its military history and three main phases of logistics development: non-integrated logistics, supply chain and networks have also been described. Although, because of its nature, logistics should be perceived and managed as a system, it has not always been the rule. The conclusion of this paper is that the more advanced the logistics evolution phase, the more system oriented its management.